Experimental Investigation of Zinc Antimonide Thin Film Thermoelectric Element over Wide Range of Operating Conditions. Issue 11 (25th August 2017) - Mirhosseini, Mojtaba; Rezania, Alireza; Blichfeld, Anders B.; Iversen, Bo B.; Rosendahl, Lasse A.
Abstract : Zinc antimonide compounds are among the most efficient thermoelectric (TE) materials with exceptional low thermal conductivity at moderate temperatures up to 350 °C. This study aims to evaluate the performance of a zinc antimonide thin film TE deposited on an insulating substrate, while the heat flows in plane with the thin film. At first, the effect of applying different temperatures at the hot side of the specimen is investigated to reach steady state in an open circuit analysis. Then, the study focuses on performance and stability analysis of the thermoelectric element operating under different resistive loads and over a wide range of operating temperatures from 160 to 350 °C. The results show that at a hot side temperature equal to 275 °C the Seebeck coefficient ( α ) reaches its maximum value (242 µV K −1 ), which is comparable to that of bulk materials reported in the literature. According to a variation of the load resistance, the maximum power output, that is a function of temperature, occurs at 170.25 Ω. The maximum power is 8.46 µW corresponding to a cold and hot side temperature of ≈30 and 350 °C, respectively. Abstract : The present study investigates the performance of a zinc antimonide specimen as a p‐type leg of a TE module under transient as well as steady state thermal boundary condition close to practical conditions. The specimen is a rectangular thin film with the length and width equal to 19.8 and 17.2 mm, respectively.